1,10-Phenanthrolin-1-ium hydrogen (S,S)-tartrate trihydrate and a correction - Derikvand, Zohreh (International Union of Crystallography, 2009)
The title structure, C(12)H(9)N(2) (+)·C(4)H(5)O(6) (−)·3H(2)O, shows that one of the protons of d-tartaric acid has been transferred to 1,10-phenanthroline. The d-hydrogen tartrate anions are joined together in a head-to-tail fashion via a short hydrogen bond with donor–acceptor distance of 2.4554 (12) Å, unsymmetrical O—H distances of 1.01 (4) Å and 1.45 (4) Å, and a 174 (4)° O—H—O bond angle. The phenanthrolinium rings are π-stacked with an average separation of 3.58 (11) Å. The structural report corrects a previous report in the literature [Wang et al. (2006 ▶). Acta Cryst. E62, o2508–o2509] of the isostructural l-hydrogen tartrate enantiomer in which the proton transfer and short hydrogen bond were missed.